2010
DOI: 10.1590/s1679-78252010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Response of vertical pile group subjected to horizontal cyclic load in soft clay

Abstract: The environment prevalent in ocean necessitates the piles supporting offshore structures to be designed against lateral cyclic loading initiated by wave action. Such quasi-static load reversal induces deterioration in the strength and stiffness of the soil-pile system introducing progressive reduction in the bearing capacity as well as the pile head displacement. To understand the effect of lateral cyclic load on lateral capacity of pile group in soft clay, a series of laboratory experiments were performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…Cracks will occur in the soil at the front side of the pile, while the clay at the rear side suffers from heave, which continues to produce a gap around the pile. This behavior well agreed with the results presented by Basack [6]. 2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cracks will occur in the soil at the front side of the pile, while the clay at the rear side suffers from heave, which continues to produce a gap around the pile. This behavior well agreed with the results presented by Basack [6]. 2.…”
Section: Discussionsupporting
confidence: 93%
“…Basak [6] studied the response of pile group (2×2) subjected to cyclic lateral load in soft clay. The experimental model was designed in such a manner that the cyclic loading test could be performed under both conditions, load-controlled and displacement-controlled modes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pile degradation factor (D p ) decreases with an increase in L c following a curvilinear pattern with an increasing slope. This observation is reasonable because an increase in the value of the torsional cyclic amplitude or cyclic loading level is likely to cause the failure of more number of elements (which is initiated by the rapid yielding of soil adjacent to the soil-pile interface) (Basack, 2010b). It must be noted that the reduction factor R f shows insignificant effect on the soil-pile interactive performance.…”
Section: Parametric Studies: Analysis and Interpretationmentioning
confidence: 86%
“…The Authors agree that preparation of a perfectly uniform test bed of clay in the laboratory should be done by remoulding the clay-water mixture at moisture content slightly higher to the liquid limit and then consolidating it to the desired state (Som 1993, Al-Mhaidib 2006a, 2007, although the water content is progressively reduced due to consolidation. The other alternative is to fill up and compact the test tank in layers with the clay water mixture (Narasimha , Basack 2010, Chandrasekaran et al 2010. It has been observed that the variation of the strength and stiffness of the remoulded test bed in the latter method is insignificant.…”
Section: Laboratory Model Testsmentioning
confidence: 99%